2019
DOI: 10.1016/j.conb.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Neural populations for maintaining body fluid balance

Abstract: Fine balance between loss-of water and gain-of water is essential for maintaining body fluid homeostasis. The development of neural manipulation and mapping tools has opened up new avenues to dissect the neural circuits underlying body fluid regulation. Recent studies have identified several nodes in the brain that positively and negatively regulate thirst. The next step forward would be to elucidate how neural populations interact with each other to control drinking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…This indicates that CB 1 receptors are necessary for the control of drinking behavior induced by 24-h water deprivation. Water deprivation triggers both intracellular and extracellular dehydration that can promote water intake through different specific pathways [1][2][3][4][5]. To discriminate the impact of CB 1 receptor signaling on either of these mechanisms, we first applied systemic (intraperitoneal [i.p.])…”
Section: Results Cb 1 Receptors Are Necessary For the Control Of Stim...mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that CB 1 receptors are necessary for the control of drinking behavior induced by 24-h water deprivation. Water deprivation triggers both intracellular and extracellular dehydration that can promote water intake through different specific pathways [1][2][3][4][5]. To discriminate the impact of CB 1 receptor signaling on either of these mechanisms, we first applied systemic (intraperitoneal [i.p.])…”
Section: Results Cb 1 Receptors Are Necessary For the Control Of Stim...mentioning
confidence: 99%
“…NaCl administration (Figures 1B, 1C, and S1F). Extracellular dehydration promotes the production of angiotensin II (Ang II), which can induce drinking behavior and salt appetite [1][2][3][4][5]. Notably, the water intake induced by the i.c.v.…”
Section: Results Cb 1 Receptors Are Necessary For the Control Of Stim...mentioning
confidence: 99%
“…Thus, optimized ingestive behavior is important for survival and well-being. Modern neurotechnologies have brought us a better understanding of neural circuits underlying body fluid and energy balance at the anatomical and functional level (Gizowski and Bourque, 2018;Ichiki et al, 2019;Lowell, 2019). As summarized in this review, appetite circuits for different nutrients (energy, water, and sodium) receive unique combinations of sensory modulation that arise from different parts of the body (Andermann and Lowell, 2017;Augustine et al, 2018b;Johnson and Thunhorst, 1997;Zimmerman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Water appetite causes animals to search for and drink water in order to restore the water-sodium balance to their physiological set points 12 , 13 . Previous studies demonstrated that thirst-driving systems are located in the forebrain sensory circumventricular organs (sCVOs) 2 , 11 , 13 16 , such as the subfornical organ (SFO) 17 and organum vasculosum of the lamina terminalis (OVLT) 18 , at which the blood–brain barrier is absent 14 : The SFO and OVLT are sensing sites for multiple thirst-driving signals, such as hypertonicity, sodium concentrations, and circulating angiotensin II (Ang II) in body fluids 19 21 . Local injections of Ang II into the SFO and OVLT, in which Ang II receptor 1a (AT1a) is positive, immediately elicited water drinking 21 24 .…”
Section: Introductionmentioning
confidence: 99%